Communication Gear Shift - Ralph J. Ballew; John E. Culp (Journal of Applied Communications, 1972)
At 8:30 A.M. the telephone rang. It was the signal that telephone communication had been established between the international trainees at TVA and Gardner Advertising Co., St. Louis.